ANALISIS SANKSI EKONOMI OLEH AMERIKA SERIKAT TERHADAP KUBA PASCA-REVOLUSI HINGGA AKHIR PERANG DINGIN (1960-1991): PERSPEKTIF CARL SCHMITT TENTANG STATE OF EXCEPTION - Suwarto, Nicholas Peter (FEB Universitas Sam Ratulangi Manado, 2024)
This research is motivated by the revolution initiated when Fidel Castro led resistance against the government ofPresident Fulgencio Batista, who had previously staged a coup against the general election in 1952. Following therevolution in Cuba, Fidel Castro, as the new head of government, transformed Cuba's system of governance to bebased on the principles of communism. Observing the impact of the adoption of communism under Fidel Castro'sadministration, the United States decided to impose economic sanctions on Cuba. The purpose of this study is toexplore how the imposition of economic sanctions on Cuba can be understood through the perspective of CarlSchmitt's “State of Exception.” To address this, the author employs Carl Schmitt’s concept of the